Ethics and Public Health: definition of priorities in the Mexican Health Reform - Gómez Dantés, Octavio; Frenk, Julio (Acta Bioethica, 2020)
The purpose of this paper is to discuss one of the most common ethical predicaments faced by public health practitioners: the distribution of limited resources for health. The question we address is the following: If there are limited resources to provide necessary health care, how can we reasonably establish priorities? We discuss this question using as reference a real-life situation, which was the establishment of priorities in the design of a package of high-cost interventions for Seguro Popular in Mexico, a public insurance scheme that extended social protection in health to over 50 million people between 2003 and 2018. The main conclusion of this paper is that the use of explicit ethical assumptions in the design of public policies contribute to their acceptability and eventual success.